Analyzing the Influence of Corporation Social Responsibility Behavior on Enterprises and Educational Equity - Kou, Danfei (Transactions on Economics, Business and Management Research, 2024)
This paper explores the role of corporate social responsibility (CSR) in promoting educational equity, using the case of TAL Education Group during the COVID-19 pandemic. TAL's initiatives, such as the "suspend classes but not stop studying" project, have provided online education solutions to millions of students, ensuring access to quality education despite disruptions. The study examines how CSR activities not only enhance educational fairness but also build brand loyalty, attract high-quality talent, and improve corporate competitiveness. Through case analysis, this research highlights the impact of public welfare activities on both corporate and social development. While TAL has made significant strides, challenges remain, such as adapting to policy changes like China's "double reduction" policy. The paper concludes with recommendations for optimizing CSR strategies, including leveraging business advantages and expanding public welfare initiatives to enhance market awareness and attract talent. Future research could explore the long-term effects of CSR on educational equity and corporate sustainability.